THE EFFECK OF NO-PERFORMING LOAN (NPL),OPERATING COSTS OPERATING INCOME(BOPO) AND CASH RATI(CR) ON COMPANY PROFIT (Empirical Study on Conventional Bank BPR Listed in OJK Riau 2014-2018) - Meka Desinta; Sri Mulyani; Arman Arman (STIE Bangkinang Publishing, 2021)
This research was conducted to examine the effect of the variable Non Performing Loan (NPL), Operational Costs and Operating Income Cash Ratio on Company Profits. The sampling technique used was purposive using the criteria: conventional rural banks which are categorized as healthy, and which have complete financial reports at OJK. The analysis technique used is multiple regression with the least squares equation and hypothesis testing using t-statistics to test the partial regression coefficient. and also statistics to test the correctness of the effect simultaneously at the 0.05 significance level. Others also perform classic assumption tests which include normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. During the study period it is displayed as normally distributed research data. Based on the multicollinearity test, heteroscedasticity test and autocorrelation test variables that deviate from the classical assumptions have not been found to indicate that the available data has met the requirements to use a multi-linear regression model. The analysis shows that the NPL, OEOI and Cash Ratio data are simultaneously significant to company profits.